KOMITMEN ORGANISASIONAL SEBAGAI PEMEDIASI PENGARUH KEPEMIMPINAN ETIS TERHADAP KEPUASAN KERJA - Satyawadi, I Gusti Ngurah Agung Eka Martha; sudibya, i gde adnyana (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.07.NO.06.TAHUN 2018DO - 10.24843/EEB.2018.v07.i06.p10, 2018)
The purpose of this study is to explain the influence of ethical leadership and organizational commitment to job satisfaction and to know the role of organizational commitment in mediating the influence of ethical leadership on job satisfaction. The populatio used in this study was all permanent employees at DharmawYadnya Hospital and used a sample of 98 people using saturated sample method. DataRwere analyzed using Partial Least Squares. The results of the study found that ethical leadership and organizational commitment partially have a positive and significant effect on job satisfaction. Furthermore, organizational commitment is found to mediate ethical leadership to job satisfaction. The implications of this study to improve job satisfaction with regard to the ethical leadership of the director or management have not disciplined employees who violate ethical standards, so directors or management utilize absentees to deduct employee salaries or provide warnings. Decision making procedures in the company also have not created a fair and balanced perception related to the objective or not the decisions taken by the director or management thus need to do transparasi related information.